A laparoscopic approach to address massive splenomegaly, symptomatic cholelithiasis, and a planned postoperative pregnancy: A case report. Issue 1 (23rd January 2023) - Bishop, Alexandra A.; Krohn, Eric; Vakayil, Victor R.; Pribyl, Kyle; Reding, Mark T.; Tignanelli, Christopher; Harmon, James V.
Abstract: We report long‐term follow‐up of a patient who underwent a tailored laparoscopic procedure for symptomatic cholelithiasis, massive splenomegaly, and a planned pregnancy. There were no complications, and the patient remained symptom‐free at the 5‐year follow‐up. We supplemented our case report with national surgical data demonstrating the safety of laparoscopic splenectomy. Abstract : Laparoscopic splenectomy is a safe and effective approach for patients with immune thrombocytopenic purpura, even those with massive splenomegaly. We highlight the benefits of tailoring the surgical approach to address the patient's surgical needs.